Physiologic principles of surgery - Zimmerman, Leo M., 1898-; Levine, Rachmiel, 1910- (Philadelphia : W. B. Saunders, 1957)
the practice of surgery has long passed beyond its anatomic derangements.
this book content , 36 chapter evry part content a spacific part of surgery , metabolic chances associated with injury -- infections and antibiotics --body fluids and electrolytes -- anesthesia the large and small intestine.
surgery. include index.
Includes bibliography.
All age.
Keywords: Surgery; Therapeutics, Surgical